Magnetic Coatings: Reconfigurable Anisotropic Coatings via Magnetic Field‐Directed Assembly and Translocation of Locking Magnetic Chains (Adv. Funct. Mater. 30/2014). (August 2014) - Tokarev, Alexander; Gu, Yu; Zakharchenko, Andrey; Trotsenko, Oleksandr; Luzinov, Igor; Kornev, Konstantin G.; Minko, Sergiy
<x xml:space="preserve">Abstract</x> A methodology for making anisotropic, reversibly reconfigurable and erasable coatings is developed by K. G. Kornev, S. Minko, and co‐workers using core–shell superparamagnetic particles with a locking behavior. On page 4738, magnetic particles are reversibly locked in the chains by adjusting the pH of the aqueous solution. The anisotropy of the coating is imposed by the external magnetic field. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>